Pendekatan Diagnosis Ensefalomielitis Diseminata Akut: Tinjauan Pustaka - Felicia - (Cermin Dunia Kedokteran, 2025)
Acute disseminated encephalomyelitis (ADEM) is an acute neurological disorder characterized by demyelination of the central nervous system (CNS). It can affect individuals of all ages, more commonly observed in boys with prior viral or bacterial infections and immunizations. ADEM typically presents with an acute and monophasic course of polyfocal neurological deficits. There are no specific symptoms in ADEM, clinical manifestations are based on the site of demyelination. Diagnosis relies on exclusion criteria as there is no definitive marker for diagnosing ADEM.